191 WALKING AND USING PEDOMETERS FOR INCREASED HEALTH. Issue 1 (1st January 2007) - Heidrich, B.
Abstract : Purpose of Study: Harborview Family Medicine Clinic has an extremely high rate of patients with hypertension, obesity, diabetes, and chronic pain. A community project was formed to try to promote low-impact exercise. The goal was to form a project that would be welcoming to all but would specifically address the needs of the previously mentioned groups. Methods: We initiated a weekly walking group in the local Harborview neighborhood. These groups were to be led by providers and myself and would occur on Friday mornings before the start of clinic. Flyers were posted in the Family Health Clinic, Puget Sound Neighborhood Health offices, Seattle Housing Authority, and Yesler Community Center. One-to-one time was spent with patients who expressed interest in exercise. All Friday morning patients were called earlier in the week and encouraged to show up early and participate in our walking group. A literature review was also performed on PubMed / MEDLINE to investigate growing trends in obesity/chronic issues and the effect that walking and pedometers can have on general health. Results: Initial participation in the group was limited. However, the group is continuing on a weekly basis, and we hope to build increased momentum. An informational sheet on walking/pedometer use was also produced and incorporated into the clinic patient health information handouts. Conclusions: Although literature review and involvement with the community can result in health promotion, many barriers exist to behavior change. Behavior change takes time; persistence and genuine cooperation are necessary if an impact is to be made.